Aesthetic Plastic Surgery of the Abdomen - Di Giuseppe, Alberto; Shiffman, Melvin A (Cham : Imprint: Springer, Imprint: Springer, 2016)
This comprehensive book covers anatomy, recent techniques, postoperative care, possible complications, and outcomes in aesthetic surgery of the abdomen. The extensive section on aesthetic procedures includes many important innovations in abdominoplasty. Detailed consideration is also given to the various potential complications, with guidance on their prevention, diagnosis, and management. The book is written by acknowledged experts in the topics on which they write. It will be of value for residents and fellows and more experienced surgeons in the fields of plastic surgery, general surgery, cosmetic surgery, and general surgery.
History -- 1.History of abdominoplasty -- 2.Muscular anatomy of the abdominal wall -- 3.Vascular and neurologic anatomy of the abdominal wall -- 4.Anatomical illustration study of the abdominal wall and fat- techniques -- 5.The impact of the menstrual cycle on intra-operative and postoperative bleeding in abdominoplasty patients -- 6.The umbilical locator -- 7.Scarpa fascia preservation during abdominoplasty -- 8.Medial advancement of infra-umbilical scarpa's fascia improves waistline definition in "brazilian" abdominoplasty -- 9.Progressive tension sutures in abdominoplasty -- 10.Evolution of the high-superior-tension lipoabdominoplasty: the high tension abdominoplasty -- 11.Lipoabdominoplasty with abdominal definition -- 12."Smile" plication abdominoplasty -- 13.Anchor line abdominoplasty -- 14.Circumferential abdominoplasty -- 15.A paradigm shift for abdominoplasty: transverse hypogastric plication without supraumbilical dissection, unrestricted liposuction, neoumbilicoplasty and low placement of the scar (tulua) -- 16.Abdominoplasty combined with cesarean section: discussion of the evidence -- 17.Lipoabdominoplasty -- 18.Modified combined lipoabdominoplasty without surgical drains -- 19.Vaser lipoabdominoplasty -- 20.Effectiveness and safety of combining laser-assisted liposuction and abdominoplasty -- 21.Abdominal contouring associated with other procedures -- 22.Modified abdominoplasty for patients with prune belly syndrome -- 23.Vaser abdominal contouring -- 24.Abdominoplasty access for desmoid tumor resection in the rectus abdominis muscle -- 25.Abdominal wall repair post hernia in kidney and liver transplantation and after gunshot wound -- 26.Abdominoplasty as the patient impetus for selection of the deep inferior epigastric artery perforator free flap donor site -- 27.Umbilicoplasty without external scar -- postoperative -- 28.Metabolic effect of abdominoplasty in the lipid profile of patients with dyslipidemia -- 29.Weight reduction following abdominoplasty -- 30.Ventilatory function in patients who underwent abdominoplasty with plication of the aponeurosis of the external oblique -- 31.C-reactive protein decrease after postbariatric abdominoplasty- complications -- 32.Complications of abdominoplasty -- 33.Retrospective analysis of never events in panniculectomy and abdominoplasty patients and their financial implications -- 34.Tension suture technique combined with lidocaine-adrenalin-saline-infiltration decreases complications in abdominoplasty -- 35.Acute abdomen after abdominoplasty: differential diagnosis -- 36.The impact of the menstrual cycle on intra-operative and postoperative bleeding in abdominoplasty patients -- 37.Maximizing chemoprophylaxis against venous thromboembolism in abdominoplasty -- 38.A study of postural changes after abdominal rectus plication abdominoplasty -- 39.Abdominoplasty complications and seroma. From prevention to effective treatment -- 40.Delayed complications in abdominoplasty: a case of a ten-year-old abdominoplasty abscess: a case of a 10-year-old abdominoplasty abscess -- 41.Acute esophageal dilation mimicking serious pulmonary complication after post-bariatric abdominoplasty -- 42.Hematological variables and iron status in abdominoplasty after bariatric surgery -- 43.Increased intraoperative bleeding in patients undergoing abdominoplasty after gastroplasty is not due to coagulopathy or vascular anatomic changes -- outcomes, satisfaction -- 44.Comparison of short-term surgical outcomes between nhs and private sector abdominoplasty surgery -- 45.Outcomes of traditional cosmetic abdominoplasty in a community setting -- 46.Long-term ultrasonographic evaluation of midline aponeurotic plication during abdominoplasty -- 47.Complications and level of satisfaction after dermolipectomy and abdominoplasty post-bariatric surgery.
Description based on publisher-supplied MARC data.
Keywords: Abdominal surgery; Plastic surgery; Surgery; Plastic Surgery; Abdominal Surgery; General Surgery